The Problem of Personal Development in the Context of Social Anomie - Hakobyan, Naira; Gevorgyan, Srbuhi; Petrosyan, Laura; Khachatryan, Anna (Տիգրան Մեծ)
The article is devoted to some prospects for personal development. In contemporary societies, personal development often occursin parallel with significant larger-scale changes of a social, socio-psychological and cultural nature. These include wars, socio-economic crises or unfavourable changes in epidemiologi-cal situations that lead to the distortion and modification of social norms and values. In such conditions, a person succumbs to uncertainty and is alienated from theirenvironment. These phenomena are character-ized by the term “social anomie”. Hence, out of all the factors contributing to personal development, pro-fessional activity significantly contributesto a person‟s ability to overcome anomie and reintegrate into society.
Keywords: Social philosophy